Near‐infrared light activated core‐shell electrospun nanofibers decorated with photoactive plasmonic nanoparticles for on‐demand smart drug delivery applications. Issue 7 (8th February 2023) - Haghighat Bayan, Mohammad Ali; Dias, Yasmin Juliane; Rinoldi, Chiara; Nakielski, Paweł; Rybak, Daniel; Truong, Yen B.; Yarin, Alexander L.; Pierini, Filippo
Abstract: Over the last few years, traditional drug delivery systems (DDSs) have been transformed into smart DDSs. Recent advancements in biomedical nanotechnology resulted in introducing stimuli‐responsiveness to drug vehicles. Nanoplatforms can enhance drug release efficacy while reducing the side effects of drugs by taking advantage of the responses to specific internal or external stimuli. In this study, we developed an electrospun nanofibrous photo‐responsive DDSs. The photo‐responsivity of the platform enables on‐demand elevated drug release. Furthermore, it can provide a sustained release profile and prevent burst release and high concentrations of drugs. A coaxial electrospinning setup paired with an electrospraying technique is used to fabricate core‐shell PVA‐PLGA nanofibers decorated with plasmonic nanoparticles. The fabricated nanofibers have a hydrophilic PVA and Rhodamine‐B (RhB) core, while the shell is hydrophobic PLGA decorated with gold nanorods (Au NRs). The presence of plasmonic nanoparticles enables the platform to twice the amount of drug release besides exhibiting a long‐term release. Investigations into the photo‐responsive release mechanism demonstrate the system's potential as a "smart" drug delivery platform. Abstract :